Measures undertaken to avoid COVID-19 Infection: Internet-based, Cross-Sectional Survey Study - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: In Saudi Arabia, over 154,000 people were infected with coronavirus disease (COVID-19). Unfortunately, until now, there are no vaccinations or effective drugs available, so only public health interventions such as physical distancing and hygiene measures in addition to targeted testing followed by isolation and quarantine measures are available. Objective: This study aims to describe the measures that are undertaken by Saudi population to avoid COVID-19 infection in Saudi Arabia. Methodology: This is a cross-sectional using internet-based survey. The survey was adapted from the previous study and from the WHO recommendations for COVID-19 prevention and control. The data included sociodemographic characteristics, level of attention, preventive measures taken by participants, and practice toward curbing the COVID-19 epidemic. Results: The majority of participants’ responded that their attention to the COVID-19 epidemics was very high to high (81.08%) while no one rated their attention at very low. To protect their families or friends, the respondents were mainly persuaded them to stay at home as much as possible (86%) and told them to avoid large gatherings (72.73%). Regarding the participants’ confidence in curbing the COVID-19 epidemic, about 73.47% of the participants were confident (strongly confident or confident). Conclusion: The public followed the hygiene recommendations of health authorities very well but still more education is still needed on some measures to prevent the spreading of the infection specially using the online education to enhance the public awareness about COVID-19.